2015
DOI: 10.1111/btp.12284
|View full text |Cite
|
Sign up to set email alerts
|

High invasive ant activity drives predation of a native butterfly larva

Abstract: Yellow crazy ants (Anoplolepis gracilipes) threaten invertebrates on many tropical islands, but little work has been done in continental ecosystems. We found 4.4-16.0 times more cruiser butterfly caterpillars were attacked in Australian rain forest sites with A. gracilipes than in native ant sites, and extrafloral nectar had little influence. , which may be more susceptible to effects of invasive species than continental ecosystems (Simberloff 1995). Only one published study has investigated effects of A. grac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The near absence of small skinks in high yellow crazy ant sites and limited differences in skink prey among site categories suggest that yellow crazy ants have directly affected the smaller skinks, rather than indirectly affected them via reducing prey. When yellow crazy ants are abundant, they are capable of harassing and, sometimes killing, invertebrate and vertebrate organisms much larger than they are (Davis et al 2010;Dorrestein et al 2019;Lach et al 2016;O'Dowd et al 2003;Plentovich et al 2018). With their formic acid spray, the ants can blind or maim organisms such as red land crabs (O'Dowd et al 2003) and wedgetail shearwater chicks (Plentovich et al 2018), and then prey on them or leave them susceptible to starvation.…”
Section: Discussionmentioning
confidence: 99%
“…The near absence of small skinks in high yellow crazy ant sites and limited differences in skink prey among site categories suggest that yellow crazy ants have directly affected the smaller skinks, rather than indirectly affected them via reducing prey. When yellow crazy ants are abundant, they are capable of harassing and, sometimes killing, invertebrate and vertebrate organisms much larger than they are (Davis et al 2010;Dorrestein et al 2019;Lach et al 2016;O'Dowd et al 2003;Plentovich et al 2018). With their formic acid spray, the ants can blind or maim organisms such as red land crabs (O'Dowd et al 2003) and wedgetail shearwater chicks (Plentovich et al 2018), and then prey on them or leave them susceptible to starvation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lach et al . () found that one ant species, Anoplolepis gracilipes , exerted 4.4–16.0 times greater predation rate than other co‐occurring ant species of tropical forests. In their study, A. gracilipes was considered to be a ‘super’ predator.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this was apparently because management of the cacao crop had negative impacts on native ants that depend on trees for nesting and foraging (Bos et al 2008 ). That A. gracilipes increases its aggressive behaviour and recruitment to foraging sites as extrafl oral nectar supply increases was used by Lach et al ( 2015 ) to evaluate its impact on an Australian native butterfl y, Vindula arsinoe (Nymphalidae) in the Wet Tropics rainforest of northern Australia. Relative ant richness in natural forest (40 species) and in cacao plantations (66 species) implied the value of the latter system, but many of the former group (treated as more specialised 'forest species') did not occur in the cacao areas.…”
Section: )mentioning
confidence: 99%